WAHDAT AL-ADYAN AND WAHDAT AL-SYUHUD SIRHINDI - Qamar, Syamsul (Program Pascasarjana, UIN Alauddin Makassar, 2020)
This writing is a study Wahdat al-Adyan and Wahdat al-Syuhud in in al-Sirhindi perspective. This is a literary research peered from various agreeable sources. The result shows that : a) The wahdāt al-adyan of al-Hallaj and wahdāt al-syuhud of Sirhindi is a derivation of lā Ilāha Illallah; b) Wahdāt al-adyan tells that all religions are essentially identical and that they have one single purpose; worship to God; c) Wahdāt al-syuhud throughout tauhid syuhudi tells an idea that all the matters came from The One. The idea, however, does not mean that everything is none.